Răspuns :
At=Al+Ab
108√3=Al+48√3
Al=108√3-48√3=60√3
Ab=l²√3/4
48√3=l²√3/4
l²=√192
l=8√3
Pb=3l=3·8√3=24√3
Al=Pb·ap/·2
60√3=24√3·ap/2
60√3=12√3·ap
ap=60√3/12√3=5
ap=5-apotema piramidei
ab-apotema bazei
ab=l√3/6=8√3·√3/624/6=4
h²=5²-4²=25-16=9
h=3
V=Ab·h/3=48√3·3/3=48√3
108√3=Al+48√3
Al=108√3-48√3=60√3
Ab=l²√3/4
48√3=l²√3/4
l²=√192
l=8√3
Pb=3l=3·8√3=24√3
Al=Pb·ap/·2
60√3=24√3·ap/2
60√3=12√3·ap
ap=60√3/12√3=5
ap=5-apotema piramidei
ab-apotema bazei
ab=l√3/6=8√3·√3/624/6=4
h²=5²-4²=25-16=9
h=3
V=Ab·h/3=48√3·3/3=48√3